(untitled) (Research, Society and Development, 2021)
Thermodynamics is linked to materials science; which studies means for obtaining new materials that have well-defined chemical and physical properties. Thermodynamics, we can say, is one of the bases of materials engineering, because the manufacturing processes of new materials involve the transfer of heat and work to the raw materials. The objective of this article is to present the applications of thermodynamics in the study of well-defined chemical and physical properties of clay materials to obtain new types of materials through a literature review.